2015
DOI: 10.1186/s13690-015-0109-5
|View full text |Cite
|
Sign up to set email alerts
|

How well do physical activity questions perform? A European cognitive testing study

Abstract: BackgroundOnly few studies have focused on the cognitive processes of the respondents that are involved when answering physical activity questionnaires (PAQs). This study aimed at examining whether two PAQs work as intended with different segments of the survey population in different cultural settings in Europe.MethodsThe International Physical Activity Questionnaire - Short Form (IPAQ-SF) and the US National Health Interview Survey - Adult Core Physical Activity Questionnaire (NHIS-PAQ) were tested in Belgiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 21 publications
0
38
0
2
Order By: Relevance
“…Each participant was asked to visit the laboratories for two sessions at least 48 hours apart. At the first session, the participants were informed about the experimental procedures and had to complete the German version of the Physical Activity Readiness Questionnaire (PARQ) which screens for individuals at increased health risk when exercising physically [14][15][16]. All individuals interested in participating in this study verified by self-reports that they were not suffering from musculoskeletal, cardiovascular, and/or neurological disorders.…”
Section: Methodsmentioning
confidence: 99%
“…Each participant was asked to visit the laboratories for two sessions at least 48 hours apart. At the first session, the participants were informed about the experimental procedures and had to complete the German version of the Physical Activity Readiness Questionnaire (PARQ) which screens for individuals at increased health risk when exercising physically [14][15][16]. All individuals interested in participating in this study verified by self-reports that they were not suffering from musculoskeletal, cardiovascular, and/or neurological disorders.…”
Section: Methodsmentioning
confidence: 99%
“…This review only included objective measures and did not include those studies that utilised PA questionnaires. Past research has shown that misreporting of PA levels in around 50% of adolescents [89] and the possibility of misinterpretation for PA questionnaires [90]. With evidence suggesting that questionnaires and the reporting of PA levels may not be accurate, such data was negated from this systematic review and meta-analysis.…”
Section: Strengths Of This Review and Meta-analysismentioning
confidence: 85%
“…The use of accelerometers would provide objective and detailed measures of physical activity, but would not be practical in such a large sample. In addition, it has been reported that, during the evaluation of physical activity practice with questionnaires, one should avoid joining different physical activity domains, as it makes it difficult for respondents to remember the activities performed, increasing error in the measurement 50,51 . However, questions similar to the one used in the present study were compared with the accelerometry, providing a reliable estimate of the physical activity behavior of adolescents 52,53 .…”
Section: Discussionmentioning
confidence: 99%